Motor imagery ability in children and adolescents with cerebral palsy: a systematic review and evidence map - Fierro-Marrero, José; Corujo-Merino, Alejandro; La Touche, Roy; Lerma-Lara, Sergio (Frontiers in Neurology, 2024)
Background: Cerebral palsy (CP) is a group of permanent movement and posture disorders. Motor imagery (MI) therapy presents potential benefits, but data on MI ability in children and adolescents with CP is lacking. Objective: A systematic review was performed exploring MI abilities in children and adolescents with CP compared to typically developed (TD) subjects. Methods: We searched 5 databases including observational studies. Methodological quality was assessed with the modified Newcastle-Ottawa Scale, evidence was synthesized qualitative and quantitatively through an evidence map. Results: Seven cross-sectional studies were selected, including 174 patients with CP and 321 TD subjects. Three studies explored explicit MI, 2 MI-Execution synchrony, and 4 implicit MI domains. Methodological quality ranged from 6-8 stars. Moderate evidence supported an absence of differences in vividness between groups. Limited evidence limited stablishing the results direction for the capacity to generate MI, mental chronometry features and MI-Execution synchrony domains. Moderate evidence supported a lower efficiency in cases for hand recognition, derived from a lower accuracy rate, and maintained reaction time across groups. Moderate evidence indicated that patients with CP and TD controls showed similar features on whole-body recognition. Conclusions: Moderate evidence suggests that patients with CP present a reduced ability in hand recognition, which is not observed for whole-body recognition compared to healthy controls. Severe limitations concerning sample size calculations and validity of assessment tools clearly limits stablishing a direction of results, especially for explicit MI and MI-Execution synchrony domains. Further research should address the aforementioned limitations to enhance our comprehension of these abilities. This is crucial for the adapted prescription of MI-based therapies in this population.